(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the study issues of systemic-structural linguistics and the different views of world and Uzbek linguists are highlighted. It is known that language is the most important means of communication between people. It is the main means of conveying information about certain events in objective existence. It turns out that there are other ways of information transfer.